Heavy Metal Toxicity in Public Health - Kanayochukwu Nduka, John; Nageeb Rashed, Mohamed (IntechOpen, 2020)
It is often said that the "dosage" of any substance determines its remedy or poison effect. Heavy metal sources encompass sewage, pesticides, fertilizers, environmental contamination, occupational exposure/contact through inhalation, ingestion, and skin. Before the advent of technology/the industrial revolution, communicable diseases ravaged the human race but this seems to have given way to non-communicable diseases such as cancers, renal failure, hormonal distortion enzymes, inhibition of fetal growth, and DNA damage causing negative health issues due to heavy metals. This book brings to the fore probably the most recent experimental research/review on heavy metal contamination, remediating techniques, cellular tissue damage, and toxicological and antioxidant effects of heavy metals. It is hoped that its contents will make interesting reading for all.